The development of the scientific bases of horticulture and the history of horticultural innovation in the Northern Great Plain region and in Debrecen - Fári, Miklós Gábor (Acta Agraria Debreceniensis, 2005)
It can be told about the second half of the XXth century that, apart from preferring the large-scale growing of field plants and the largescalelivestock farming, corresponding to the central political will of the communist era, the significance and innovation output ofhorticultural education in Debrecen was rather of follow-up trait, of secondary importance. The Tobacco Research Institute continued theresearch work, and then even this activity was stopped. According to a survey finished in 1997, the mentioned institute had no invention,granted patent, protection for registered model or any application for patent in progress at the Hungarian Patent Office. Until this time, invention activity at the University of Agricultural Sciences was of medium standard. In the National Patent Office, seven patent applications related to agricultural production and nine patent applications for other fields submitted under the inventors’ names were recorded. In the same period, the Cereal Research Institute (Szeged) led the absolute innovation list of Hungarian agricultural R+D institutions and university education institutes by submitting 164 own patent applications. Both in domestic and international terms, the horticultural innovation conducted at the University of Agricultural Sciences, despite the individual research results and achievements deserving recognition, without appropriate background – remained unnoticed. Let us put it this way: for the past decades, the light of the Debrecen Flower Carnival has not been thrown on the horticultural teachers and researchers of Debrecen.